In Aunt Giraffe's green garden - Prelutsky, Jack.; Mathers, Petra ([New York] : Greenwillow Books, 2007)
A collection of twenty-eight, humorous, children's poems written by poet laureate Jack Prelutsky. Includes illustrations.
3.6
K-3
Keywords: Animals -- Juvenile poetry; Children's poetry, American; Animals -- Poetry; American poetry; Animals -- Poetry; American poetry